Challenges from experiment: electronic structure of NiO - Kuo, Chang-Yang; Haverkort, Maurits W. (European physical journal special topics, 2017)
We report on a detailed experimental and theoretical study of the electronic structure of NiO. The charge-transfer nature of the band gap as well as the intricate interplay between local electronic correlations and band formation makes NiO to be a challenging case for a quantitative ab-initio modeling of its electronic structure. To reproduce the compensated-spin character of the first ionization state and the state created by hole doping requires a reliable determination of the charge transfer energy Delta relative to the Hubbard U. Furthermore, the presence of non-local screening processes makes it necessary to go beyond single-site many body approaches to explain the valence band spectrum.
Gesehen am 03.11.2017